Acute effects of continuous positive airway pressure in patients with obstructive sleep apnea. (2nd January 2020) - Han, Su-Hyun; Lee, Sang-Ahm
Abstract: Objectives. To enhance the initial compliance of continuous positive airway pressure (CPAP) in the patient with obstructive sleep apnea (OSA), we investigate the acute effects of one-night CPAP on morning blood pressure (BP) and, if any exist, to determine which factors predict BP-lowering effects of one-night CPAP in OSA subgroups stratified by the presence or absence of uncontrolled hypertension. Design. Newly diagnosed OSA patients (a respiratory distress index (RDI) ≥ 15) without a history of hypertension were stratified by the presence or absence of morning hypertension. Comparisons were made of morning BP, overnight change in mean BP (MBP), and circadian BP pattern (RM/E, the ratio of morning to evening MBP) between two time points of diagnostic and CPAP titrations in each subgroup. In the subgroup with a significantly reduced morning BP, predictors of changes in morning MBP were determined by multiple linear regression analyses. Results. The prevalence of morning hypertension was 48.8%. One-night CPAP reduced BP immediately only in patients with morning hypertension. By contrast, patients without morning hypertension did not experience any BP-lowering effects. In the subgroup with morning hypertension, baseline morning MBP, female sex, and RM/E were independently associated with reduced morning MBP, and RM/E was the most important predictor. Conclusions. These results confirm the acute effects of one-night CPAP on lowering BP in OSA patients with morning hypertension. An unfavorable circadian BP pattern is the most important predictor.